Seni Didong sebagai Media Dakwah Kultural Masyarakat Gayo Lues : Tinjauan Historis dan Nilai-Nilai Keislaman - Virdha Alhumairah; Muliadi Kurdi; CutRizky Meutia; Zahratun Marwah (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study aims to examine the historical development of Didong art in Gayo Lues Regency, analyze its role as a cultural identity of the Gayo community, and identify the Islamic values embedded in Didong as a medium of cultural da'wah. This research employed a qualitative method using a historical approach and library research. Data were collected through documentary studies of primary sources, including Didong lyric manuscripts, as well as secondary sources such as books, scholarly journal articles, and other relevant documents. The data were analyzed using descriptive qualitative analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that Didong has developed dynamically in response to the social, political, and cultural changes within the Gayo community. Beyond serving as a cultural identity, Didong functions as a medium of cultural da'wah by conveying the values of faith, morality, brotherhood, and education. Through its poetic lyrics and performances, Didong contributes to preserving local culture while internalizing Islamic values, making it a relevant cultural heritage for the Gayo community today.